A kinetic evaluation and optimization study on NOx reduction by reburning under pressurized oxy-combustion. (15th July 2021) - Rahman, Zia ur; Zhang, Jiaye; Zhang, Lan; Wang, Xuebin; Yang, Zhiwei; Tan, Houzhang; Axelbaum, Richard L.
Abstract: Pressurized oxy-combustion is an emerging and more efficient technology for carbon capture, utilization, and storage than the first generation (atmospheric) oxy-combustion. NOx is a major conventional pollutant produced in pressurized oxy-combustion. In pressurized oxy-combustion, the utilization of latent heat from moisture and removal of acid gases (NOx and SOx) are mainly conducted in an integrated direct-contact wash column. Recent studies have shown that NOx particular inlet concentration should be maintained before direct contact wash column to remove NOx and SOx efficiently. As a result, minimizing NOx for environmental reasons, avoiding corrosion in carbon capture, utilization, and storage, and achieving effective NOx and SOx removal in direct contact wash columns are crucial. Reburning is a capable and affordable technology for NOx reduction; however, this process is still less studied at elevated pressure, particularly in pressurized oxy-combustion. In this paper, the kinetic evaluation and optimization study on NOx reduction by reburning under pressurized oxy-combustion was conducted. First, the most suitable mechanism was selected by comparing the results of different kinetic models with the experimental data in literature at atmospheric and elevated pressures. Based on the validated mechanism, a variety of parameters were studied at high pressure, i.e., comparing the effects of oxy and the air environment, different reburning fuels, residence time, H2 O concentration, CH4 /NO ratio, and equivalence ratio on the NO reduction. The results show that de-NOx efficiency in an oxy environment is significantly enhanced compared to the air environment. Improvement in the de-NOx efficiency is considerably higher with a pressure increase of up to 10 atm, but the effect is less prominent above 10 atm. The formation of HCN is significantly reduced while the N2 formation is enhanced as the pressure increases from 1 to 10 atm. The residence time required for the maximum NO reduction decreases as the pressure increases from 1 atm to 15 atm. At the higher pressure, the NO reduction rises prominently when the ratio of CH4 /NO increases from 1 to 2; however, the effect fades after that. At higher pressure, the NO reduction by CH4 reburning decreases as the H2 O concentration increases from 0 to 35%. The optimum equivalence ratio and high pressure for maximum NO reduction are 1.5 and 10 atm, respectively. This study could provide guidance for designing and optimizing a pressurized reburning process for NOx reduction in POC systems. Highlights: Reburning for NO reduction in oxy-environment is studied at high pressure. De-NOx efficiency in oxy environment is significantly larger at higher pressure. At higher pressure the formation of HCN is reduced prominently. The N2 formation from NO is enhanced as the pressure increases from 1 to 10 atm.